Kemampuan Guru dalam Menerapkan Evaluasi Non-Tes di SDN Lengkong Karya Tangerang Selatan - Ina Magdalena; Alin Putri Dianti; Uswatun Hasanah; Eva Farhanah (Jurnal Halaqah, 2020)
All activities carried out in learning should be evaluated through appropriate instruments. Evaluation in the world of education is an absolute activity, because this evaluation develops student learning achievement in all subjects. In addition, through the evaluation of teachers involved in educational institutions can find out how far and how far the development of teaching programs to achieve the goals formulated. The purpose of this study was to determine whether teachers at SDN Lengkong Karya applied non-test evaluations. The results of this study show that teachers at SDN Lengkong Karya have not been able to use non-test evaluations due to several factors.